Validity evidence for Croatian version of the Conditional Reasoning Test for Aggression - Galić, Zvonimir (Array, 2014)
The Conditional Reasoning Test for Aggression (CRT-A) is based on the idea that aggressive individuals use motive-based cognitive biases to see their behavior as reasonable and that those biases can be measured with inductive reasoning tasks. Although the initial validation efforts for the CRT-A in the United States have been reasonably successful, there has been no attempt to determine if the evidence of validity and reliability generalizes to other cultural contexts. In this paper, we describe four studies designed to systematically accumulate validity evidence for the CRT-A using Croatian participants. Our analyses revealed that the Croatian adaptation of the CRT-A yielded psychometric characteristics that were similar to those obtained on the US samples (Study 1). CRT-A scores that predicted counterproductive work behaviors occurrence beyond self-reported personality (Study 2) were independent from general mental ability as measured with an abstract reasoning test (Study 3), and not susceptible to faking (Study 4).